Schmidt-hammer exposure-age dating of seven paraglacial rock-slope failures in the Bolungarvík-Suðureyri area (Westfjords, Iceland) - Portier, Emilie; Mercier, Denis; Decaulne, Armelle; Cossart, Etienne (Geomorphology, 2024)
International audience Many rock-slope failures (RSF) impact Iceland's Westfjords morphology. Five RSF areas, totalling seven RSFs, were studied in the western fjords around Bolungarvík-Suðureyri: Óshólar, Minni-Hlið, Meira-Hraun, the Vatnadalur valley and part of the Sunddalur valley.The aim of this article is to provide chronological data of the RSFs and to subsequently obtain a better chronosequence of post-glacial events, none of which have yet been dated in the Westfjords. More particularly, we discuss a paraglacial hypothesis of their occurrence.For this purpose, the Schmidt-hammer exposure-age dating (SHD) method is used on the RSF deposits, and the rebound values obtained from the impacted blocks are converted to age estimates using radiocarbon ages obtained from the different sites in order to calculate a SHD age calibration. Then, we establish a chronology of the setting up of the events. In this way, seven RSFs have been dated and different chronological generations of deposit emplacement have been exhibited for some of them. Thus, various periods of instability affected mountain slopes. The Óshólar RSF is thought to have been deposited firstly at around 12,500 cal BP, the Minni-Hlið RSF at ~9800 cal BP, the Meira-Hraun RSF at ~8700 cal BP, the Vatnadalur RSFs at ~9000 cal BP, ~ 6900 cal BP, and ~ 4300 cal BP, and the Sunddalur RSF at ~9600 cal BP. These RSFs therefore correspond to so-called paraglacial events, which took place at the beginning of deglaciation of the area during the first half of the Holocene.